E-COMMERCE SEBAGAI STRATEGI PEMASARAN USAHA KECIL DAN MENENGAH DALAM MENINGKATKAN KEUNGGULAN BERSAING PADA LEVEL MARKETING ASEAN - Sultoni, Mohammad Hamim (IQTISHODUNA, 2015)
Facing ASEAN Economic Community 2015, SMEs in Indonesia should have competence andcompetitive advantage as the key to face competition for trading in ASEAN levels. The competitivenessexpected is including quality of the product aspect, access for information of marketing and resources.Because of that, this research has a goal to know the role of E-Commerce with a case study of SMEs in MalangCity. Research Method used is field observation in some SMEs that have implemented E-Commerce as MarketingStrategy. Results of the research indicate that the significant role of E-Commerce to the improvement of marketaccess of SMEs in Malang. The biggest influence is on improvement sales of products and the expansion ofnew market shares. In the future, this research is expected to be an overview of the importance utilization of Ecommerce.The lack of knowledge of E-commerce strategy and access for marketing information for SMEs inIndonesia became one of the problems that must be resolved in facing AEC 2015.